MODELLING ISLAMIC HOTEL RELATIONSHIP BETWEEN SERVICESCAPE AND CUSTOMER SATISFACTION IN KLANG VALLEY: EVIDENCE FROM PLS-SEM AND IPMA ANALYSIS - Ong, Mohd Hanafi Azman; Hamid, Rasidah; Burhanudin, Muhamad Addin; Razak, Intan Rahayu Abdul (International Journal of Supply Chain Management, 2019)
Malaysia is a country that consists of various regions in which the official region is Islam. Therefore, Malaysia is known as a popular destination for Muslim tourist to visit to and as for that there is opportunity for Malaysia to develop Islamic Hotel concept in order to fulfill the demand of Muslim tourist. Understanding the consumer attitudes towards Islamic Hotel should be the guideline for marketers in strategizing the marketing tactics. The objective of this study is to provide and insight consumers options towards Islamic hotel by measuring the service scape of the hotel which been divided into three segments which are ambiance, interior design and facilities. A questionnaire survey has been distributed for this study and result showed that there are several aspects under each of segments that can lead to customer satisfaction by using the PLS-SEM and IPMA analysis. The findings in this study can be used by other hotel operators to have a thoughtful mind on the factors that driven customersâ?? preferences and satisfaction that will aid in designing a message with better persuasion and at the same time attract more tourists to come and visit Malaysia.